Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.reprotox.2013.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disruption in male mice due to fetal exposure to low but not high doses of bisphenol A (BPA): Evidence for effects on body weight, food intake, adipocytes, leptin, adiponectin, insulin and glucose regulation

Abstract: Exposure to bisphenol A (BPA) is implicated in many aspects of metabolic disease in humans and experimental animals. We fed pregnant CD-1 mice BPA at doses ranging from 5 to 50,000 μg/kg/day, spanning 10-fold below the reference dose to 10-fold above the currently predicted no adverse effect level (NOAEL). At BPA doses below the NOAEL that resulted in average unconjugated BPA between 2 and 200pg/ml in fetal serum (AUC0–24h),we observed significant effects in adult male offspring: an age-related change in food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
170
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(207 citation statements)
references
References 92 publications
19
170
3
5
Order By: Relevance
“…Our data can be considered additional evidence that BPA at low doses may act not only via ERa but also by activating non-canonical ER pathways. The up-regulation of leptin mRNA levels is very intriguing and agrees with the results of a previous study (Angle et al 2013). Leptin production by adipocytes is proportional to their fat content; leptin serum levels are higher in obese subjects, and are directly correlated to adipose mass and adipocyte contents (Fried et al 2000, Yang & Barouch 2007.…”
Section: Discussionsupporting
confidence: 89%
“…Our data can be considered additional evidence that BPA at low doses may act not only via ERa but also by activating non-canonical ER pathways. The up-regulation of leptin mRNA levels is very intriguing and agrees with the results of a previous study (Angle et al 2013). Leptin production by adipocytes is proportional to their fat content; leptin serum levels are higher in obese subjects, and are directly correlated to adipose mass and adipocyte contents (Fried et al 2000, Yang & Barouch 2007.…”
Section: Discussionsupporting
confidence: 89%
“…Further research using fetal liver tissue has also identified specific relationships between BPA and repetitive DNA elements, where nonmonotonic relationships between BPA exposure and DNA methylation were observed in several repeat families, including LINE1 [78]. Nonmonotonic relationships have previously been observed in prenatal mouse exposure models both with respect to both epigenomic and metabolic end points [79][80][81]. However, previous research, using both LUMA and pyrosequencing, did not identify a relationship between global methylation and BPA exposure in fetal liver or kidney, but did note a positive relationship between BPA exposure and LINE1 methylation in the placenta [82].…”
Section: Endocrine Disruptorsmentioning
confidence: 86%
“…Additional studies are needed to assess the occurrence, frequency, and implicated endpoints for NMDRCs in in vivo studies of BPA and for other EDCs. NMDRCs have been reported for BPA in a number of studies of laboratory animals (see for example (Angle et al, 2013;Ayyanan et al, 2011;Cabaton et al, 2011;Jenkins et al, 2011;Marmugi et al, 2012;Xu et al, 2010)), but the majority of studies examining rodents or aquatic animals have used fewer than six doses (Richter et al, 2007;vom Saal and Hughes, 2005;Welshons et al, 2006), and thus NMDRCs are likely to be more difficult to observe or detect.…”
Section: Non-monotonicity Is Common For In Vitro Studies Of Bpamentioning
confidence: 99%